2020
DOI: 10.1371/journal.pone.0244273
|View full text |Cite
|
Sign up to set email alerts
|

Does social trust slow down or speed up the transmission of COVID-19?

Abstract: Social trust has been an important mechanism in overcoming crises throughout history. Several societies are now emphasizing its role in combating the COVID-19 pandemic. This study aims to investigate how variations in social trust across 68 countries are related to the transmission speed of COVID-19. Specifically, using cross-national index data from the World Value Survey, the study tests how variations in social trust across countries generate different time durations at which each country reaches the peak i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 42 publications
1
30
0
1
Order By: Relevance
“…In two preliminary studies on individual perceptions and awareness during the early stage of Covid-19 in the US and Finland, the trust and confidence in political authorities’ actions to prevent the outbreak was quite low [ 1 , 25 ] while more recent studies showed that the implementation of restrictive measures increased trust in the government, especially for individuals who didn’t experience the disease, directly or indirectly [ 26 , 27 ]. An interesting study conducted in Serbia during the first wave of the Covid-19 pandemic assessed the influence of conspiracy beliefs and political trust on adherence to COVID-19 preventive behaviour [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In two preliminary studies on individual perceptions and awareness during the early stage of Covid-19 in the US and Finland, the trust and confidence in political authorities’ actions to prevent the outbreak was quite low [ 1 , 25 ] while more recent studies showed that the implementation of restrictive measures increased trust in the government, especially for individuals who didn’t experience the disease, directly or indirectly [ 26 , 27 ]. An interesting study conducted in Serbia during the first wave of the Covid-19 pandemic assessed the influence of conspiracy beliefs and political trust on adherence to COVID-19 preventive behaviour [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in addition to the direct effect of risk perception on intentions to limit one’s behavior [ 3 , 5 , 6 , 23 ], we expected a mediating role of the (interpersonal and institutional) trust variable on this relationship [ 24 , 25 , 26 , 27 , 28 ]. Thus, we expected that an increase in risk perception would correspond to an increase in precautionary behavior intentions in the participants, at the same time as an increase in the trust component (interpersonal and institutional).…”
Section: Introductionmentioning
confidence: 99%
“…There of course remains lots of unexplained variance, recognizing that environmental factors such as temperature (21), humidity (21), and UV exposure (22) may affect the spread of COVID-19, and that different strains of COVID-19 differ in their basic reproduction number (8). Despite all this we find a marked effect of trust, which adds to evidence that trust can support increased COVID-19 risk perception (23), decreased mortality early in the pandemic (24), and an earlier peak of new infections (25). Before the pandemic, the rise of neoliberalism since the 1980s and austerity policies since the 2008/9 financial crash had eroded the social contract between citizens and government in many nations (15).…”
Section: Main Textmentioning
confidence: 53%
“…As people may have different reasons beyond health and scientific literacy to resist mask recommendations, trustworthiness may be necessary to facilitate the public's willingness to tolerate uncertainty and to voluntarily accept behavioural guidance or comply with government-imposed mandates in a pandemic. International data on social trust suggests that while people in high-trust societies initially had more frequent in-person interactions that led to quicker viral spread, high cooperation to achieve the common goal to halt the spread had allowed those countries to neutralize COVID-19 faster once the danger was recognized and clearly communicated (Min 2020). In contrast, distrust of public health experts and their advice can have serious health and socio-economic consequences not only for the individuals disregarding such advice but also for the broader population (Bennett 2020).…”
Section: Trustworthiness In a Pandemicmentioning
confidence: 99%